2022
DOI: 10.2172/1886660
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Benefits and Challenges of Converting Retiring Coal Plants into Nuclear Plants

Abstract: A coal-to-nuclear (C2N) transition means siting a nuclear reactor at the site of a recently retired coal power plant. Three overarching questions from the C2N transition guide this research: where in the United States are retired coal facilities located and what factors make a site feasible for transition; what factors of technology, cost, and project timeline drive investor economics over such a decision; and how will C2N impact local communities?The study team evaluated the siting characteristics of recently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 11 publications
(28 reference statements)
0
31
0
1
Order By: Relevance
“…This provides a higher-level of fidelity that can be needed for certain analyses. For instance, if existing infrastructure can be leveraged and not all costs need to be accounted in the cost (e.g., in the case of leverage the switchyard for a 'coal-to-nuclear' transition for instance [3]). Another scenario where this level of detail is needed is in the case of a heat-only use case where the cost of the turbine and associated systems does not need to be included.…”
Section: Sources and Methodology For Cost Estimationmentioning
confidence: 99%
“…This provides a higher-level of fidelity that can be needed for certain analyses. For instance, if existing infrastructure can be leveraged and not all costs need to be accounted in the cost (e.g., in the case of leverage the switchyard for a 'coal-to-nuclear' transition for instance [3]). Another scenario where this level of detail is needed is in the case of a heat-only use case where the cost of the turbine and associated systems does not need to be included.…”
Section: Sources and Methodology For Cost Estimationmentioning
confidence: 99%
“…The U.S. Department of Energy (DOE) released a report demonstrating that 157 retired coal plant sites and 237 operating coal plant sites are potential candidates for a coal-tonuclear transition. The corresponding study indicated that 80% of analyzed plants are good candidates for hosting advanced reactors operating under the gigawatt scale [67]. Analyses of the technical and economic effects of the integration of nuclear units based on a fluoride-salt-cooled high-temperature reactor, KP-FHR, on repowering an existing coal plant in Poland have already been presented [68].…”
Section: Approaches In Site Selection: Large-scale Npp Units Vs Smrsmentioning
confidence: 99%
“…As recommended in the EPRI Siting Guide, the evaluation leveraged a graded approach when assessing the suitability of the CGS site and nearby SRP owned land for a nuclear generating station 4 .…”
Section: Cgs Siting Evaluation Approachmentioning
confidence: 99%
“…Decision Planning: During this stage, more detail/investigation is required to assess siting considerations and develop a deployment schedule to plan/coordinate information gathering and siting activities. At this point of the process, utilities have confirmed that the site(s) of interest do not have any exclusionary factors and have plans to assess risks associated with any avoidance factors identified during the Exclusionary/Avoidance 4 It is important to note that this initial siting evaluation is focused on a site of interest (i.e., the CGS site) versus a region of interest due to the unique opportunities associated with repowering the CGS site. As a result, to satisfy NRC requirements, SRP will need to evaluate alternative sites to justify the selection of CGS during future stages (see Reference 3).…”
mentioning
confidence: 99%